Cortical Activation during a Cognitive Challenge in Patients with Chronic Temporal Lobe Epilepsy—A Dynamic SPECT Study - P. J. Kirkpatrick; R. Morris; G. M. S. Syed; C. E. Polkey (Behavioural Neurology)
In a pilot group of six patients suffering from chronic temporal lobe epilepsy, single photon emission computerized tomography (SPECT) has been used to image the changes in relative cerebral blood flow between rest (static scan) and conditions of cognitive activation (activated scan). The cognitive challenge used during activation comprised a test of word memory, and the performance was expressed as a word memory score (WMS) for each individual. An activation index (AI) was calculated from the mean normalized density counts in specific regions of interest (ROIs), and values obtained were analysed for correlation with the WMS. The mean AI was increased significantly in the right lateral temporal cortex, the right and left inferior frontal regions, the left temporal pole, and the right medial temporal cortex. A positive correlation with the WMS was found in the medial temporal cortices, and this relationship was significant for the right medial temporal ROI.